Accuracy of a modified World Health Organization Disability Assessment Schedule 2.0 as an assessment tool for predicting return-to-work among patients with traumatic brain injury. Issue 23 (5th November 2020) - Huang, Shih-Wei; Chang, Kwang-Hwa; Escorpizo, Reuben; Liou, Tsan-Hon
Abstract: Purpose: Patients with traumatic brain injury often experience cognition-related problems and difficulty in returning to work. This study analyzed the accuracy of a modified version of World Health Organization Disability Assessment Schedule 2.0 for predicting the return-to-work status of working-age patients diagnosed with traumatic brain injury more than 6 months ago. Materials and methods: We conducted a cross-sectional survey from a nationwide disability database. This study analyzed the data of 1312 patients diagnosed with traumatic brain injury (aged 20–60 years) more than 6 months ago from the Taiwan Data Bank of Persons with Disability for the period from July 2012 to January 2014. The demographic data and modified World Health Organization Disability Assessment Schedule 2.0 standardized scores of patients with traumatic brain injury who could and could not return to work (return-to-work and nonreturn-to-work groups, respectively) were analyzed. Receiver operating characteristic curve analysis was performed to investigate the prediction accuracy of the modified World Health Organization Disability Assessment Schedule 2.0 for predicting the return-to-work status, and the optimal cutoff point was determined using the Youden index. Binary logistic regression was used to determine the predictors of the return-to-work status of the participants. Results: The modified World Health Organization Disability Assessment Schedule 2.0 scores in all domains were lower in the return-to-work group than in the nonreturn-to-work group. Receiver operating characteristic analysis revealed the high accuracy of the summary scores of the modified World Health Organization Disability Assessment Schedule 2.0 (area under the curve >0.8). Binary logistic regression revealed that patients with standardized modified World Health Organization Disability Assessment Schedule 2.0 summary scores less than 39.50 were 11.20 (95% confidence interval, 4.80–26.14; p < 0.001) times more likely to return to work than patients with scores more than 39.50. Conclusions: The modified World Health Organization Disability Assessment Schedule 2.0 can be used as an objective and reliable assessment tool for predicting the return-to-work status of working-age patients with traumatic brain injury. This tool can facilitate goal setting and rehabilitation strategy design to enable patients with traumatic brain injury to return to work. Implications for rehabilitation: Summary scores of six domains of a modified World Health Organization Disability Assessment Schedule 2.0 had better accuracy of predicting the opportunity to return to work among traumatic brain injury patients than each domain. Sex, education level and severity of impairment were related to the opportunity to return to work in traumatic brain injury patients. Higher disability scores from a modified version of the World Health Organization Disability Assessment Schedule 2.0 were associated with less opportunity to return to work and can be referenced for establishing effective rehabilitation strategies for facilitating return to work among persons with traumatic brain injury.